2023
DOI: 10.1523/eneuro.0361-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Impacts Nucleus Accumbens Dopamine Dynamics

Abstract: Circadian photoperiod, or day length, changes with the seasons and influences behavior to allow animals to adapt to their environment. Photoperiod is also associated with seasonal rhythms of affective state, as evidenced by seasonality of several neuropsychiatric disorders. Interestingly, seasonality tends to be more prevalent in women for affective disorders such as Major Depressive Disorder and Bipolar Disorder. However, the underlying neurobiological processes contributing to sex-linked seasonality of affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 99 publications
1
12
1
Order By: Relevance
“…A previous study using rats has shown sex differences in magnitude of DA release between males and females, with evoked accumbal DA release being greater in females compared with males because of greater DA synthesis in females 33,48,49 . However, these studies were all done in rats, whereas our work here and others carried out in mice have found no sex differences 50 . The lack of differences in DA uptake across the rostro‐caudal axis and across sexes suggests that there is no difference in DAT expression or function.…”
Section: Discussioncontrasting
confidence: 68%
“…A previous study using rats has shown sex differences in magnitude of DA release between males and females, with evoked accumbal DA release being greater in females compared with males because of greater DA synthesis in females 33,48,49 . However, these studies were all done in rats, whereas our work here and others carried out in mice have found no sex differences 50 . The lack of differences in DA uptake across the rostro‐caudal axis and across sexes suggests that there is no difference in DAT expression or function.…”
Section: Discussioncontrasting
confidence: 68%
“…16 Interestingly, a recent study showed that mice maintained in a long, summer-like photoperiod showed higher dopamine release in the ventral striatum as compared to the control condition. 17 Extrapolating this finding to humans, one may speculate that higher synaptic dopamine is by higher DAT expression. Seasonal oscillations in the dopaminergic system in PD have also previously been shown using [ 18 F]F-DOPA PET with right putaminal dopamine synthesis capacity being 15% higher when the patients were scanned in autumn/winter compared to spring/summer.…”
Section: Discussionmentioning
confidence: 93%
“…The DAT plays a major role in the regulation of synaptic dopamine levels by taking up synaptic dopamine back into dopaminergic neurons 16 . Interestingly, a recent study showed that mice maintained in a long, summer‐like photoperiod showed higher dopamine release in the ventral striatum as compared to the control condition 17 . Extrapolating this finding to humans, one may speculate that higher synaptic dopamine is compensated by higher DAT expression.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have used RNAseq to characterize differential gene rhythmicity and differential gene expression in response to Short winter-like photoperiods vs. Long summer-like photoperiods. To best capture the impact of photoperiod, we used a strain of mice (C3Hf+/+, Baba et al, 2009) which possess intact melatonin signaling, and we used perinatal exposure to photoperiods, which we have previously shown to produce robust plasticity in the SCN and robust photoperiodic responses in downstream serotonergic and dopaminergic brain circuits (Ciarleglio et al, 2010;Giannoni-Guzmán et al, 2020;Green et al, 2015;Jameson et al, 2023;Siemann et al, 2019Siemann et al, , 2020. Our approach reveals specific gene expression changes in SCN neuropeptide signaling and light response genes as candidate novel molecular mechanisms for SCN light response plasticity and SCN neural network reconfiguration in photoperiodic entrainment.…”
Section: Introductionmentioning
confidence: 99%